O livro e a leitura na imprensa maranhense de educação e ensino (1902-1932) - BORGES, Almicéia Larissa Diniz (2017)
This paper presents the relevance of reading and reading in the Maranhão schools in the first republican decade from the education and teaching press, especially in the newspapers of primary education institutions. The period chosen (1902-1932) was due to the fact that the new configurations in the Brazilian political and educational scenario with the Proclamation of the Republic that influenced the educational transformations, in this period newspapers were scenarios for the dissemination of new discourses on education. The objective is to understand the discourses about the book and reading in these newspapers and what their role in the school and non-school context, because through these manuals was transmitted a knowledge that should be taught to the students and at the same time served as a pedagogical support of teachers about what should be taught. It should be noted that these discourses were not restricted only to the school book, but also to the non-school book. Therefore, understanding the thinking about these materialities allows us to understand the importance of them in and out of school, whether they were viewed positively or negatively and their relationship with teaching. This research is based on two moments: in first moment, the bibliographical survey of the authors that approach the book and the reading Abreu (1999), Belo (2002), Chartier (1988, 2001, 2010), Lajolo, Zilberman (2002) Velasquez (2012); and the education and teaching press, among them: Bastos, Catani (1997), Castro (2008), Nóvoa (1993), Furtado (2016). In the second moment a documentary research, in the case the newspapers of these institutions of primary education referring to the years of 1900-1930, found in the Digital Collection of the Public Library Benedito Leite. It was preliminarily concluded that these journals were used as a way of criticizing subjects related to teaching, especially those that referred to the methods of reading and the importance of reading in the formation of the individual. This research aims to contribute to the studies related to the History of Education, History of the book, History of the Press.